2018
DOI: 10.3390/ijms19061644
|View full text |Cite
|
Sign up to set email alerts
|

Butterbur Leaves Attenuate Memory Impairment and Neuronal Cell Damage in Amyloid Beta-Induced Alzheimer’s Disease Models

Abstract: Alzheimer’s disease (AD) is the most prevalent neurodegenerative disease, and is characterized by the accumulation of amyloid beta (Aβ) as a pathological hallmark. Aβ plays a central role in neuronal degeneration and synaptic dysfunction through the generation of excessive oxidative stress. In the present study, we explored whether leaves of Petasites japonicus (Siebold & Zucc.) Maxim. (PL), called butterbur and traditionally used in folk medicine, show neuroprotective action against Aβ25–35 plaque neurotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Studies have shown in both cellular and animal models that oxidative stress upregulates the expression and activity of BACE1 through the activation of the c-Jun N-terminal kinase/activator protein1 pathway [58,59,60,61]. Kim et al reported that treating SK-N-MC cells with palmitic acid conjugated with bovine serum albumin (PA-BSA) results in an increased expression of BACE1 and Aβ production through the G protein-coupled receptor 40 (GPCR40) [62].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown in both cellular and animal models that oxidative stress upregulates the expression and activity of BACE1 through the activation of the c-Jun N-terminal kinase/activator protein1 pathway [58,59,60,61]. Kim et al reported that treating SK-N-MC cells with palmitic acid conjugated with bovine serum albumin (PA-BSA) results in an increased expression of BACE1 and Aβ production through the G protein-coupled receptor 40 (GPCR40) [62].…”
Section: Discussionmentioning
confidence: 99%
“…Safety evaluations are critical when new compounds/foods are introduced to the marketplace [24,25]. In our preliminary studies, we elucidated two new lignans and isolated six known compounds from KP-1 that showed neuroprotective and anti-inflammatory effects [9,10]. PL extracts are used as medicines in the West.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated the neuroprotective effects of hot water extracts of P. japonicus leaves (KP-1) in Aβ 25-35 -plaque-induced Alzheimer's disease models. KP-1 protects hippocampal cells against Aβ 25-35 plaque toxicity by regulating intracellular reactive oxygen species (ROS) levels and in vitro activation of cAMP response element-binding protein (CREB)induced antioxidant enzymes [10]. Development of and research on pharmaceutical and functional foods using natural products are actively progressing, which reinforces the need for safety assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse anti-synaptophysin (SYP) and the other reagents were purchased from Sigma-Aldrich (St. Louis, MO, USA) unless noted. Aβ 25–35 was purchased from AnaSpec (Fremont, CA, USA) and reconstituted in sterile water at a concentration of 500 μM and incubated at 37 °C for 72 hours to form amyloid plaque as previously described [23].…”
Section: Methodsmentioning
confidence: 99%